ChemInform Abstract: Solid‐Phase Capture for the Detection and Relative Quantification of S‐Nitrosoproteins by Mass Spectrometry. Issue 22 (3rd June 2014) - Thompson, J. Will; Forrester, Michael T.; Moseley, M. Arthur; Foster, Matthew W.
Abstract Review: 55 refs.